(untitled) (Research, Society and Development, 2021)
Bisphosphonates are drugs that act by decreasing and inhibiting osteoclastic activity, and inducing cell apoptosis. They block osteoclast differentiation and stimulate osteoblasts, resulting in decreased bone resorption. It may contribute to the exposure of necrotic bone in the maxillofacial region. Thus, this narrative review proposes a brief discussion about the development of osteonecrosis of the maxillary bones resulting from therapy with bisphosphonates. Having as the theme the development of osteonecrosis in the jaws resulting from the use of bisphosphonates, we searched through the MeSH terms and DeCS/MeSH terms, between 2006 and 2021, for articles in English and Portuguese indexed in the MEDLINE/PubMed database, Web of Science, LILACS/bvs as well as through a manual search. After analysis the selected articles, it was observed that the possibility of the development of osteonecrosis in the maxillary bones is multifactorial, thus it is imperative to approach these sites with a preventive way and with a minimally invasive therapy.